Is City Marketing Opposed to Urban Planning? The Elaboration of a Pilot City Marketing Plan for the Case of Nea Ionia, Magnesia, Greece - Alex Deffner; Theodoros Metaxas (European Regional Science Association (ERSA), 2006)
The role of city marketing has been increasingly important in Europe. Today it has become a necessity with regard to the processes of global competition of cities, tourist attraction, urban management, city branding and urban governance. Many European cities support their competitiveness through cultural and tourism development. In addition, the majority of the implemented city marketing policies relate with culture and tourism. City marketing has faced many criticisms, the main one being that it substitutes for urban planning. However, the work done in cultural planning indicates that, in order for cities to be successful, marketing must be inter-connected with planning. There are even international examples of cities that have elaborated marketing plans in order to attract the potential target markets (new investments, tourists, new residents etc). One recent approach argues that marketing can contribute to the sense of place. The data for this paper are provided by the INTERREG IIIc CultMark project (Cultural Heritage, Local Identity and Place Marketing for Sustainable Development) that has been in operation in five European places since 2004: Nea Ionia/ Magnesia/ Greece (lead partner), Chester/ UK, Kainuu/ Finland, Rostock-TLM/ Germany and Pafos/ Cyprus. The CultMark project is applying a place marketing strategy with a cultural approach. This means that it emphasizes the cultural dimension of marketing and the promotion of the cultural resources of each place. The innovative characteristics of this project are reinforced by the use of the two concepts of 'creativity', and 'branding destination'. The main objective of the CultMark project is the development and implementation of innovative place marketing strategies, based on the elements of local identity and the cultural assets of the partner areas in order to contribute to their sustainable economic and social development. As a case study the elaboration of the marketing plan of Nea Ionia/ Magnesia/ Greece is chosen, and the aim of the paper is to show the interconnection of marketing and planning by trying to answer, among others, the following questions: a) does marketing planning constitute strategic planning?, b) how can marketing contribute to sustainability?, c) can cultural heritage be marketed?
Keywords: 330